D-1 Gene Polymorphism in Salivary Gland Tumors - Ghapanchi, Jannan; Samavatian, Behnam; Ghaderi, Hamid; Khademi, Bijan; Mahmoudi Maymand, Elham; Ainy, Elaheh (Journal of Dental School, 2019)
Objectives This study aimed to assess PD-1gene polymorphism in salivary gland tumors in patients referred to Khalili Hospital in Shiraz. Methods This case-control study evaluated 48 patients with salivary gland tumors and 100 age- and sex-matched healthy controls. First, 5cc blood samples were obtained from patients and transferred to vials containing anti-coagulated EDTA. DNA was extracted, and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was performed on the samples. The PD-1 gene genotype was determined using the Fermentas kit. After 24 hours of incubation, all the samples were electrophoresed. The genotypes were reported based on the size of bands, and the chi-square test was applied. To compare the alleles, the Fisher’s Exact test was applied. The Yates correction was used to compare the genotype and genotypic alleles based on the tumor grade. Results The mean age was 44.81±15.69 years in patients and 46.54± 13.86 years in controls. Statistical analysis did not show any significant difference in PD1 gene polymorphism between the two groups (P=0.098). No significant correlation was found between the genotype frequency and lymph node involvement (P=0.06), tumor genotype (P=0.12), side (right or left) (P=0.22), tumor location (P=0.27), and size or invasion of the tumor to the surrounding tissue (P=0.14). PD1.3 genotype frequency did not differ significantly between malignant and benign tumors (P=0.6). Conclusion This study did not reveal any significant difference in genotype frequency of PD1.3 in the patient and control groups; however, further studies are needed with a larger sample size to obtain more accurate results.